Penanaman Nilai-Nilai Pancasila pada Usia Dini Studi Kasus di PAUD Al Ghifari Tasikmalaya - Gustaman, Randy Fadillah; Rosita, Lilis (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2023)
Abstract. Education is the right path to develop children's potential, in accordance with the values in the life of the nation and state. At the age of early childhood, which is a golden period in their development, PAUD Al Ghifari is an educational institution that focuses on early childhood with many students. As an institution that produces basic human resources, the institution has an obligation to instill Pancasila values from an early age. Some forms of Pancasila value cultivation integrated in the formal curriculum include the habituation of prayer at the beginning and end of activities, the introduction of ceremonies to commemorate national holidays, and the habituation of love for cleanliness and the environment. In addition, educators at PAUD Al Ghifari also use hidden strategies such as modeling good behavior and providing examples to children.